Family involvement, patient safety and suicide prevention in mental healthcare: ethnographic study. Issue 2 (23rd March 2023) - Gorman, Louise S.; Littlewood, Donna L.; Quinlivan, Leah; Monaghan, Elizabeth; Smith, Jonathan; Barlow, Stephen; Webb, Roger T.; Kapur, Navneet
Abstract : Background: Family involvement has been identified as a key aspect of clinical practice that may help to prevent suicide. Aims: To investigate how families can be effectively involved in supporting a patient accessing crisis mental health services. Method: A multi-site ethnographic investigation was undertaken with two crisis resolution home treatment teams in England. Data included 27 observations of clinical practice and interviews with 6 patients, 4 family members, and 13 healthcare professionals. Data were analysed using framework analysis. Results: Three overarching themes described how families and carers are involved in mental healthcare. Families played a key role in keeping patients safe by reducing access to means of self-harm. They also provided useful contextual information to healthcare professionals delivering the service. However, delivering a home-based service can be challenging in the absence of a supportive family environment or because of practical problems such as the lack of suitable private spaces within the home. At an organisational level, service design and delivery can be adjusted to promote family involvement. Conclusions: Findings from this study indicate that better communication and dissemination of safety and care plans, shared learning, signposting to carer groups and support for carers may facilitate better family involvement. Organisationally, offering flexible appointment times and alternative spaces for appointments may help improve services for patients.